Determinants of the nurses' and nursing assistants' request for antipsychotics for people with dementia. (21st November 2016) - Janus, Sarah I. M.; van Manen, Jeannette G.; IJzerman, Maarten J.; Bisseling, Marloes; Drossaert, Constance H. C.; Zuidema, Sytse U.
ABSTRACT: Background: Although physicians are responsible for writing the antipsychotic prescriptions for patients with dementia, the initiative is often taken by nurses or nursing assistants. To reduce antipsychotics uses, one needs to understand the reasons for nurses and nursing assistants to request them. This study gives an overview of the influencing factors for this request based on the Theory of Planned Behavior in which attitude, beliefs, and behavioral control is thought to influence the intention to request, which in turn affects the behavior to request for a prescription. Methods: Eighty-one nurses and nursing assistants of one Dutch nursing home organization completed an online survey. Results: Nurses and nursing assistants frequently agreed on items related to the positive effects of antipsychotics for the resident and for the staff. Nurses and nursing assistants with a lower job satisfaction were more likely to call for antipsychotics. Having more positive beliefs about treatment effects and feel of being more in control toward asking for antipsychotics were positively associated with intention to call. All variables explained 59% of the variance of intention. The current position (nurse/nursing assistant) was associated with actual behavior to call. The explained variance was 25%. Conclusions: Policy-makers should focus on the nurses' and nursing assistants' belief in positive effects of antipsychotics for the resident, which is not in line with available evidence. Nurses and nursing assistants should be educated about the limited effectiveness of antipsychotics.